Gender imbalances limit water and energy management in Uzbekistan - Alvi, Muzna; Sufian, Farha (CGIAR System Organization, 2024)
NEXUS Gains conducted a household survey with over 1,800 small farming households in four regions in Uzbekistan. The survey covered crop economics, climate change experiences and adaptation strategies, and adoption of water-saving technologies. It also included the project-level Women’s Empowerment in Agriculture Index (Pro-WEAI) and questions on women’s decision-making over energy choices. This study was the first to use the Pro-WEAI in Uzbekistan, following similar surveys in India, Pakistan, and Nepal under NEXUS Gains. This has enabled the creation of a regional gender-disaggregated database covering the Indus, Aral Sea, and Ganges basins.